2018
DOI: 10.5114/hm.2018.77322
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of cardiopulmonary parameters in archery performance

Abstract: Purpose. The aim of this investigation was to determine the most significant cardiopulmonary parameters bound with high archery scores and to assess their relationship with successful performance in archery. Methods. The total of 32 archers with mean age of 17 ± 0.56 years were gathered from dissimilar archery programmes. Cardiopulmonary parameters were measured prior to shooting tests. Multivariate techniques of principal component analysis (PCA), hierarchical agglomerative cluster analysis (HACA), and discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The effect of cardiovascular fitness in sports has been widely acknowledged by scholars (19,20). Based on the results of this study, it was reported that cardiovascular fitness is positively correlated with archery performance.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of cardiovascular fitness in sports has been widely acknowledged by scholars (19,20). Based on the results of this study, it was reported that cardiovascular fitness is positively correlated with archery performance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, another possible explanation for the relationship between pulmonary functions and shooting performance may be due to the fact that pulmonary capacity can affect breathholding time. Some previous studies demonstrate links between shooting performance and lung capacities in archers [98,99]. However, another study showed no correlation between air pistol shooting performance and pulmonary function in shooters competing in the young female category (age 16) [12].…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to compress a high dimensional dataset into a lower dimensional dataset. Recent study also revealed PCA is particularly useful when data on a number of useful variables has been gathered, and it is plausible that there is some redundancy in those variables [25][26][27][28][29]. Table 1 shows the descriptive statistics of anthropometric measurement and physical fitness among 600 male participants.…”
Section: Discussionmentioning
confidence: 99%